2010
DOI: 10.1111/j.1600-0447.2009.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of female sex workers

Abstract: Sex work is a major public health problem. It has many faces, but ill mental health of sex workers is primarily related to different forms of violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
124
1
22

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 40 publications
(41 reference statements)
8
124
1
22
Order By: Relevance
“…According to GSI results, almost two-thirds of the sex workers experienced significantly moderate to severe disorder symptoms more than women in the control group. These results are in line with the studies in Hong Kong and France (21,22), but in contrast with the findings of a study in New Zealand, which found no significant difference between sex workers and other women with respect to general wellbeing (23). The results of another study on FSWs in the USA found that more than one-third of the participants suffered from anxiety symptoms and more than half of them had depression symptoms (24).…”
Section: Discussioncontrasting
confidence: 56%
“…According to GSI results, almost two-thirds of the sex workers experienced significantly moderate to severe disorder symptoms more than women in the control group. These results are in line with the studies in Hong Kong and France (21,22), but in contrast with the findings of a study in New Zealand, which found no significant difference between sex workers and other women with respect to general wellbeing (23). The results of another study on FSWs in the USA found that more than one-third of the participants suffered from anxiety symptoms and more than half of them had depression symptoms (24).…”
Section: Discussioncontrasting
confidence: 56%
“…The study by Hoigard and Finstad is controversial because it is said to be biased towards a radical feminist point of view and because it focuses on prostitution on the street and in brothels. However, although the incidence of PTSD, depression, and self-hatred appears to differ depending on the segment analyzed (street, brothel, private, escorts and subsegments thereof), the average incidence of these mental conditions across segments is clearly high (see Rössler et al, 2010 for an interesting study using clusters). It has to be noted, however, that prostitutes in specific segments do appear to be perfectly healthy.…”
Section: The Harmmentioning
confidence: 99%
“…Statistics also reveal something in this regard. In their Zurich study, Rössler et al (2010) found that about 40% of the prostitutes they studied declared that they actually liked the job. Abel similarly comments that "some participants in this [New Zealand] study spoke of being 5 See, e.g., Hoigard and Finstad (1992), Abel (2010) and Rössler et al (2010).…”
Section: The Harmmentioning
confidence: 99%
See 2 more Smart Citations